A conceptual history of disasters. Metaphorical knowledge as a possibility for floods risk management in El Valle La Estrella, Limón, Costa Rica - Coto-Cedeño, Wainer Ignacio (2024)
This article has got two objectives. The first analyzes, from history perspective, the experiences of population's El Valle La Estrella and their relationship with floods, territory and the Comité Comunal de Emergencias de El Valle La Estrella [CCEVE]. The second analyzes the member experiences of disaster risk management. The investigation was built based on interdisciplinary strategy; said strategy connected methods and techniques of anthropology, sociology, linguistics, and history. Specifically, the investigation used to oral history, ethnography, pragmatics, speech analysis and content analysis. Also, it was used to interviews to collect testimonials. The main conclusion is that metaphorical knowledge shows an unfinished hydro-social cycle where citizen and territorial management acts as a trigger for social disputes